Aevedo Tarzona, Álvaro. The Historical experience of the co-government in the Universidad Insdustrial de Santander. Concepts and divergences in the dispute for university autonomy. 1971-1976. Bucaramanga: Ediciones Universidad Industrial de Santander, 230 - Diaz Jaramillo, José Abelardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Reseña